Integrated Analysis of Water Quality in Treatment Plants: Physicochemical and Biological Assessments: Analisis Terpadu Kualitas Air di Instalasi Pengolahan: Penilaian Fisikokimia dan Biologis - Pratama, Aditya Yoga; Marodiyah, Inggit (Procedia of Engineering and Life Science, 2024)
Water treatment plants (WTPs) play a crucial role in ensuring access to safe drinking water, essential for human health and well-being. This study focuses on the IPA Kedunguling, operated by the Regional Drinking Water Company Sidoarjo, which serves the residents of Sidoarjo city. The objective was to evaluate the water treatment process and quality using physical, chemical, and biological assessments in accordance with Ministry of Health Regulation No. 2/2023 and Government Regulation No. 66/2014. The process involves raw water intake at the Intake, followed by treatment at the WTP and distribution to residents. Laboratory tests revealed that chemical and biological parameters met regulatory standards; however, Total Dissolved Solid (TDS) levels exceeded permissible limits, highlighting a potential area for improvement. This study underscores the importance of continuous monitoring and optimization of water treatment processes to ensure the provision of safe drinking water to communities. Highlights : Water treatment plants ensure access to safe drinking water, vital for human health. Evaluation of IPA Kedunguling's water treatment process and quality according to regulatory standards. Laboratory tests identify areas for improvement, particularly in Total Dissolved Solid levels. Keywords: Water treatment plants, water quality assessment, regulatory compliance, drinking water safety, continuous monitoring.